Pengukur Berat dan Tinggi Baadan Iideal Berbasis Arduino - Nuryanto, Rudi (2016)
Have an ideal body weight or normal is the desire of every person to look proportional. Many of us encounter in health clinics, and a gym, people who are considering weight and height to gauge the scale tool to determine whether their weight is ideal or not. For those who do not know the ideal weight calculation formula will be difficult to determine the ideal weight for him. The purpose of this study was to determine the weight and the ideal height with ease. This study uses the Arduino UNO as the main controller, ultrasonic sensors as inputs high reader and sensor load cell for heavy inputs, as well as a 20X4 LCD viewer screen. Three buttons are used as a start button (start), view results, and reset. 12 volt power supply is used as a voltage source. How to use this measure to rise to the means of scales or boards footing, and the measurement results will be instantly displayed on the LCD viewer. Testing is done by means of experimental measurements five times. Average error in height measurement was 0.40% for the 15 constants, 1.32% to 7 constants, and 31.71% for no constants. Average error in the measurement of body weight is 0.65%. Average error on the measurement of IMT was 0.17% for height and weight to 0.86%.